2000
DOI: 10.1002/(sici)1096-9071(200005)61:1<52::aid-jmv8>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the GBV-C/hepatitis G virus is primarily a lymphotropic virus

Abstract: GB virus-C and the hepatitis G virus (GBV-C/HGV) are variants of the same positive sense RNA flavivirus, initially thought to be associated with hepatitis. The tissue tropism of GBV-C/HGV in normal subjects has not been evaluated to date using an extended tissue spectrum. Therefore, the sites of GBV-C/HGV replication were investigated in serum and twenty-three tissues collected during post-mortem examination of four apparently healthy individuals who died accidental deaths, who were infected with GBV-C/HGV. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 49 publications
1
47
0
Order By: Relevance
“…GBV-C RNA is commonly detected in bone marrow and spleen tissue (10, 11), and GBV-C has been demonstrated to replicate in vitro in peripheral blood mononuclear cells, particularly B and T lymphocytes (12, 13). Chronic GBV-C infection has been associated with decreased apoptosis of T cells, impaired T cell activation and proliferation, and changes in immune responsiveness which may contribute to lymphomagenesis (1416).…”
Section: Introductionmentioning
confidence: 99%
“…GBV-C RNA is commonly detected in bone marrow and spleen tissue (10, 11), and GBV-C has been demonstrated to replicate in vitro in peripheral blood mononuclear cells, particularly B and T lymphocytes (12, 13). Chronic GBV-C infection has been associated with decreased apoptosis of T cells, impaired T cell activation and proliferation, and changes in immune responsiveness which may contribute to lymphomagenesis (1416).…”
Section: Introductionmentioning
confidence: 99%
“…However, as a result of several large epidemiological studies there was no evidence for the association of GBV-C infection and hepatitis (Alter et al, 1997a(Alter et al, , 1997b. Moreover, several research groups have documented GBV-C to be not hepatotropic (Laskus et al, 1997(Laskus et al, , 1998Pessoa et al, 1998) but primarily lymphotropic (Tucker et al, 2000). In vitro studies have shown that GBV-C is able to productively infect PBMC (Fogeda et al, 1999;George et al, 2003) and Xiang et al (2000) could show that in vitro transfection of primary CD4+ T lymphocytes with a full length GBV-C RNA led to active viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to HCV, GBV-C does not appear to be hepatotrophic as the virus neither replicates in hepatocytes nor causes acute or chronic hepatitis (Alter, 1997;Laskus et al, 1997). In fact, GBV-C is a lymphotrophic virus that is believed to replicate primarily in the spleen and bone marrow (Tucker et al, 2000). There is also some evidence that the virus replicates in a number of different peripheral blood mononuclear cells, including CD4 positive T cells (Xiang et al, 2000).…”
mentioning
confidence: 99%